Evolutionary game of international trade network based on trade policy differences - Jun Zheng; Junfang Wang; Aizhong Shen (Scientific Reports)
Abstract Trade policy differences among different countries are important factors affecting international trade cooperation. In this paper, we build an evolutionary game model of international trade in which complex networks portray game relationships and trade policy differences are game strategies of players. Compared with the fully coupled game relationship and two-strategies game, the game relationship dynamic adjustment, trade policy differences and stochastic game payoffs in this paper are more in line with the real international trade context. We use mathematical analyses and computer simulation methods to reveal the impact of trade policy differences on the game payoffs of countries and the overall international trade networks. The results show that the reduce of the tolerance “t” of fair-trade is difficult to eliminate the opportunism trade policy and lead to a decline in the game payoffs of all countries and the global trading network. Dynamic adjustment of trade relations can not only improve the game payoffs of all countries and the trade network, but also offset the negative impact of the decline of the tolerance “t”. In terms of long-term, only the win-win trade policy can maximize the payoffs of the global trade network and achieve a balanced distribution of trade benefits.